Taenia solium taeniasis and cysticercosis control and elimination through community-based interventions - Carabin, Hélène (Curr Trop Med Rep, 2014)
Taenia solium was declared potentially eradicable by the International Task Force for Disease Eradication in 1992. Yet, very few well-designed community-based randomized controlled trials have been conducted to measure the effectiveness of alternative control strategies. Most strategies have been tested in pre-post intervention designs in very few communities, often without a control group. The only two community-based randomized controlled trials suggest that an educational program alone or a combination of human and porcine mass treatment reduce porcine cysticercosis in the short term. A transmission dynamics model suggests that improved sanitation and pig management are more effective and sustainable than pig vaccination, human or porcine mass treatment. Current evidence does not support the eradication of Taenia solium in the foreseeable future. Investigators should follow international recommendations on the conduct of community-based randomized control trials to provide more valid estimates of the effect and cost-effectiveness of alternative control strategies for cysticercosis.